Projections of extreme rainfall and floods in Mediterranean basins from an ensemble of convection-permitting models - Poncet, Nils; Tramblay, Yves; Lucas-Picher, Philippe; Thirel, Guillaume; Caillaud, Cécile (Climatic Change, 2025)
Floods have major impacts on the Mediterranean region, but little is currently known about their potential evolution in the context of climate change. This is due in particular to the limited ability of climate models to reproduce extreme meteorological events such as heavy rains that lead to flash floods, especially at the local scale over smaller basins. This study is the first to explore future flood scenarios over 12 Mediterranean basins using an ensemble of 12 high-resolution convection-permitting climate models and the GR5H hourly rainfall-runoff model. The results indicate an overall increase in flood intensity across all basins, particularly for the most severe events, but also a strong spatial variability in the change signal depending on the geographic location. There is good agreement among the convection-permitting climate models on an increase in hourly and daily rainfall extremes in the Mediterranean, but these changes are not strongly correlated with changes in flood-peak intensity, indicating that change in rainfall intensity alone is a poor predictor of future flood hazards. At present, this type of analysis is hampered by the short duration of the available high-resolution climate simulations. Longer timeseries would be required to better assess the robustness of the projected changes against climate variability.
Keywords: Infolettre_Septembre_2025

Will Evolving Climate Conditions Increase the Risk of Floods of the Large U.S.‐Canada Transboundary Richelieu River Basin? - Lucas‐Picher, Philippe; Lachance‐Cloutier, Simon; Arsenault, Richard; Poulin, Annie; Ricard, Simon; Turcotte, Richard; Brissette, François (JAWRA Journal of the American Water Resources Association, 2021)
Abstract In spring 2011, an unprecedented flood hit the complex eastern United States (U.S.)–Canada transboundary Lake Champlain–Richelieu River (LCRR) Basin, destructing properties and inducing negative impacts on agriculture and fish habitats. The damages, covered by the Governments of Canada and the U.S., were estimated to C$90M. This natural disaster motivated the study of mitigation measures to prevent such disasters from reoccurring. When evaluating flood risks, long‐term evolving climate change should be taken into account to adopt mitigation measures that will remain relevant in the future. To assess the impacts of climate change on flood risks of the LCRR basin, three bias‐corrected multi‐resolution ensembles of climate projections for two greenhouse gas concentration scenarios were used to force a state‐of‐the‐art, high‐resolution, distributed hydrological model. The analysis of the hydrological simulations indicates that the 20‐year return period flood (corresponding to a medium flood) should decrease between 8% and 35% for the end of the 21st Century (2070–2099) time horizon and for the high‐emission scenario representative concentration pathway (RCP) 8.5. The reduction in flood risks is explained by a decrease in snow accumulation and an increase in evapotranspiration expected with the future warming of the region. Nevertheless, due to the large climate inter‐annual variability, short‐term flood probabilities should remain similar to those experienced in the recent past.